Travel Journal Application as an Android-Based Traveling Visitor Using Firebase - Wijaya, Ricky Yohanes; Saputra, Nova Andre; Trisno, Indra Budi (JISA(Jurnal Informatika dan Sains), 2023)
Traveling is an activity that people do today to take a break from work, study or just enjoy the beauty of nature. But sometimes people forget whether they have visited a certain place. Photos in their gallery, which are not organized in their smartphone's internal storage and are not accompanied by a placemark, will cause someone to forget exactly what happened in a place. In this study, an Android-based application recording system will be designed to make the traveler who wanted to take photos during their vacation easy. This application uses real-time Firebase database features, Mapbox maps API, and GPS technology to differentiate between every photo was being taken. Firebase has the ability to automatically update changes made by one user to another and notify them simultaneously. This feature is useful for sharing happy moments with friends on the trip. And this application will send a reminder again when they visit a place not far from the one they are currently visiting.